For small (1-3cm) nonfunctional adrenal incidentaloma (NFAI), which option is more appropriate for conservative treatment or surgery? - Li, Xuwen; Xiao, Song; Zhan, Xiangpeng; Yu, Yue; Zhang, Cheng; Xi, Haibo; Wang, Gongxian; Zhou, Xiaochen (Frontiers in Endocrinology, 2023)
Objective: To compare the efficacy and safety between conservative treatment and surgery for the patients with small (1-3cm) nonfunctional adrenal incidentaloma (NFAI). Methods: The patients with small (1-3cm) NFAI who received conservative treatment or surgery in our hospital from November 2018 to December 2019 were retrospectively collected. A total of 83 patients were included in this study. They were divided into two groups according to the treatment methods: the surgery group (n=51) and the conservative treatment group (n=32).Then patients’ demographics, tumor characteristics, functional indicators and complications were compared. Statistical analysis was performed using t-test for continuous variables and Pearson chi-square test or Fisher’s exact test for categorical variables. Results: At the time of diagnosis, after 3 months, after 6 months, after 12 months, and after 24 months, we found that there was no significant difference between the two groups in systolic blood pressure, diastolic blood pressure, serum potassium levels, and hormone levels. 51 patients chose to have surgery, of which 41 patients chose RLA and 10 patients chose RARLA. RARLA group patients had the highest total cost and conservative treatment group patients had the lowest cost, and the difference was significant (P < 0.001). There was no significant difference in tumor size in the conservative treatment group between at the time of diagnosis and after 24 months (P = 0.305). Conclusion: Surgical treatment is more effective for 1-3cm NFAI, but conservative treatment is safer and more economical. Follow-up after conservative or surgical treatment is necessary.